2004
DOI: 10.1093/brain/awh194
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with social developmental disorders prosopagnosic? Perceptual heterogeneity in the Asperger and socio-emotional processing disorders

Abstract: It has been hypothesized that social developmental disorders (SDD) like autism, Asperger's disorder and the social-emotional processing disorder may be associated with prosopagnosic-like deficits in face recognition. We studied the ability to recognize famous faces in 24 adults with a variety of SDD diagnoses. We also measured their ability to discriminate changes in internal facial configuration, a perceptual function that is important in face recognition, and their imagery for famous faces, an index of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 58 publications
8
65
1
Order By: Relevance
“…This view is also supported by a recent study that shows that face recognition is not correlated with ratings of social impairment nor does it line up with a particular diagnosis of social developmental disorder. Instead, as we do, the authors argue that any difficulties in face processing in individuals with social deficits may well be causally related to an underlying perceptual alteration, suggestive of occipitotemporal dysfunction (Barton et al, 2004). Whether the perceptual alteration is primarily responsible for the local bias and/or difficulty to derive configuration or whether it comes from lack of experience with faces remains to be determined.…”
Section: Preference For Local Information In Autismmentioning
confidence: 64%
“…This view is also supported by a recent study that shows that face recognition is not correlated with ratings of social impairment nor does it line up with a particular diagnosis of social developmental disorder. Instead, as we do, the authors argue that any difficulties in face processing in individuals with social deficits may well be causally related to an underlying perceptual alteration, suggestive of occipitotemporal dysfunction (Barton et al, 2004). Whether the perceptual alteration is primarily responsible for the local bias and/or difficulty to derive configuration or whether it comes from lack of experience with faces remains to be determined.…”
Section: Preference For Local Information In Autismmentioning
confidence: 64%
“…In particular, support may be useful for young people who need to establish a new set of social relationships at school, college, university, or work, if they lack confidence in managing the social difficulties caused by DP. Prosopagnosia may also contribute to the difficulties of some people with autism spectrum disorders [12].…”
Section: Discussionmentioning
confidence: 99%
“…Since DP interferes with social interaction it might predispose some people to develop social anxiety disorder, which is characterized by fear and avoidance of social situations which have the potential to cause embarrassment or humiliation [10,11]. It has even been suggested that DP could contribute to some cases of social developmental disorder [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have assessed the performance of affected individuals using standardized neuropsychological tests of face processing have reported impairments relative to controls [Barton et al, 2004;De Gelder et al, 1991;Klin et al, 1999;McPartland et al, 2004], no impairments [Adolphs et al, 2001;Smalley and Asarnow, 1990] or impairments in memory for faces, but not in face discrimination [Howard et al, 2000]. The quality of the behavioral studies varies considerably: a variety of experimental designs have been utilized, stimulus presentation has generally been poorly controlled and sample sizes have often been small.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have included nonface objects as control stimuli have found that affected individuals were unimpaired [Hauck et al, 1998;Teunisse and de Gelder, 2003] or showed superior object-processing performance [Blair et al, 2002;Boucher and Lewis, 1992]. The combination of impaired face and intact object processing has led to the proposal that individuals with ASD fail to use secondorder configural [Barton et al, 2004;Davies et al, 1994;Teunisse and de Gelder, 2003] or holistic [Deruelle et al, 2004;Joseph and Tanaka, 2003;Lopez et al, 2004;Serra et al, 2003;Teunisse and Degelder, 1994] information for face discrimination, but instead rely on feature processing [Davies et al, 1994;Deruelle et al, 2004;Lahaie et al, 2006;Langdell, 1978]. Additionally, the paired observations of impaired configural processing and intact or superior feature processing have been interpreted by some researchers [Davies et al, 1994;Deruelle et al, 2004] as supporting the weak central coherence theory of ASD, which claims that individuals with ASD have a general cognitive style of focussing on the parts of visual stimuli rather than the contextual whole [Happe and Frith, 2006;Frith, 1983, 1993].…”
Section: Introductionmentioning
confidence: 99%